Решите уравнение 1) (6 – x)3 – x²(16 – x) = 2x2 + 116;
2) (y + 7)3 + y(13 – y) = 21y2 + 23

mariyakarimova2 mariyakarimova2    2   02.02.2021 00:14    4

Ответы
b00777 b00777  02.02.2021 01:00
Пошаговое объяснение:
(6 - x)³ - x² (16 - x) = 2x² + 116,
216 - 108х + 18х² - х³ - 16х² + х³ = 2х² + 116,
216 - 108х + 18х² - 16х² - 2х² - 116 = 0,
216 - 108х - 116 = 0,
108х = 216 - 116,
108х = 100,
х = 100/108,
х = 25/27
ПОКАЗАТЬ ОТВЕТЫ
Stevejobs1111 Stevejobs1111  02.02.2021 01:00
1)204825 2)9610551

Объяснение:

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра